Fish medicine - Stoskopf, Michael K (W.B. Saunders Co., 1993)
This is one of the textbook of the North Carolina State University College of Veterinary Medicine, Raleigh. Comprehensive introductory textbook for veterinary students. 47 Contributors, predominately U.S. The book is a very thorough review of the diseases affecting fish. This book covers medicine from a taxonomic perspective, grouping diseases by the major taxonomic groups that they affect. One can look up differentials for skin diseases in a certain species without running down the entire list of bacterial, viral, etc.